Rapid and sensitive detection of Shigella sonnei in feces by the use of an O-antigen-specific monoclonal antibody in a combined immunomagnetic separation-polymerase chain reaction assay - Achí Araya, María Rosario (1996)
Reporte técnico -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 1996. Este documento es privado debido a limitaciones de derechos de autor.